Life cycle assessment of ramie fiber used for FRPs - Dong, Shaoce; Xian, Guijun; Yi, Xiao-Su (MDPI, 2018)
With the depletion of natural resources and the deterioration of environment, natural fiber based biomaterials are attracting more and more attentions. Natural fibers are considered to be renewable, biodegradable, and ecofriendly, and have been applied to be used as alternative reinforcements to traditional glass fibers for polymer based composites (GFRP). Natural fiber reinforced polymer (NFRP) composites have been found to be manufactured as secondary structures or interior parts of aircrafts or automobiles. In this paper, a cradle-to-gate life cycle assessment (LCA) study was performed to demonstrate the possible advantages of ramie fiber on environmental impacts and to provide fundamental data for the further assessment of ramie fiber reinforced polymers (RFRP) and its structures. By collecting the material inventories of the production process of ramie fiber, the environmental impacts of ramie fiber (characterized by eight main impact categories, which are climate change, terrestrial acidification, freshwater eutrophication, human toxicity potential, ozone depletion, photochemical oxidant creation, freshwater ecotoxicity, and fossil depletion) were calculated and compared with that of glass fiber. Found if spinning process is ignored within the production of the ramie fiber, ramie fiber exhibits better ozone depletion and they have almost the same values of climate change and terrestrial acidification in terms of glass fiber. However, if the spinning process is included, ramie fiber only performs better in terms of ozone depletion. And degumming and carding and spinning processes are the processes that cause more pollution